The synthesis and characterisation of confined polyoxometalates within nanostructured carbon - Kemp, Matthew G (2021)
This study reveals the confinement effects of four different polyoxometalates within graphitised carbon nanofibers. A standard ionic liquid mediation filling procedure was developed for the encapsulation of POMs within GNFs. The basic characteristics of each polyoxometalate were analysed using a wide range of analytical techniques such as FTIR, PXRD and TGA, each POM was then compared to each other to gain further understanding on how both Keggin and Wells-Dawson type polyoxometalates function under a constricted space. POMs@GNF composites were characterised via TGA, PXRD, TEM, EDX and electrochemical techniques. It was noted that precursor concentration was found to influence particle aggregation, location of POM deposition and both thermal and catalytic activity of POM@GNF composites. Besides being hollow nano-containers, GNFs can act as templates for the growth of bulk metal oxides. Preliminary electrocatalyst tests were also undertaken with some of the POM samples, indicating that on encapsulation they retain their redox based behaviour. Overall, this work provides examples of heteronuclear polyoxometalate encapsulation within GNFs and also explains how the synergistic effects between POMs and GNFs leads to an electronic coupling system in which electrons from the metallic like GNF are preferentially donated to POM guest species.